The argument-predicative structure in legal discourse - Mykhailova, O.V.; Михайлова, О.В. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2014)
The article focuses on the analysis of the argument-predicative clause structure in the official type of legal discourse with the purpose to establish mental schemes verbalized by the participants of legal communication. The application of the cognitive approach allows the explanation of the syntactic peculiarities of legal discourse. В статті розглядаються питання пов’язані з реалізацією аргументно-предикатної структури елементарного речення в текстах ділового юридичного дискурсу. Мета статті – встановити ментальні схеми за якими учасники правової комунікації висловлюють свої наміри. Застосування когнітивного підходу дозволяє пояснити синтаксичні особливості організації юридичного дискурсу. В статье рассматриваются вопросы, связанные с реализацией аргументно-предикатной структуры элементарного предложения в текстах делового вида юридического дискурса. Цель статьи – установить ментальные схемы, в соответствии с которыми, участники правовой коммуникации передают определенные смыслы. Применение когнитивного подхода позволяет объяснить синтаксические особенности организации юридического дискурса.
Аргументно-предикатна структура в юридичному дискурсі
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; adjuncts; circonstants; clause; legal discourse; mandatory syntactic argument; mental scheme; the argument-predicative structure; ад’юнкти; актанти; аргументно-предикатна структура; елементарне речення; ментальна схема; сірконстанти; юридичний дискурс